2020
DOI: 10.1007/s00384-020-03734-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of PD-L1 expression in colorectal cancer: a meta-analysis

Abstract: Purpose To systematically evaluate the correlation between PD-L1 expression and clinicopathological features and prognosis of colorectal cancer (CRC). Methods Seven databases (PubMed, Cochrane Library, EMBASE, Web of Science, CBM, Wanfang, and CNKI) were searched through May 2020. Risk of bias and quality of evidence were assessed by using the Newcastle–Ottawa scale (NOS), and meta-analysis was carried out by using the Review Manager 5.3 software on the studies with the quality evaluation scores ≥ 6. Meta-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…By performing IHC staining assay with primary and metastatic ovarian cancer tissues and survival analysis, we further proved that PD‐L1 could be regarded as a prognostic risk factor and induce ovarian cancer progression and metastasis. Previous studies have reported similar results in other types of cancer, such as head and neck cancer [41], colorectal cancer [42], endometrial cancer [43], and clear cell renal cell carcinoma [44]. PD‐L1 was also found to play a vital role as a poor prognosis predictor in patients with biliary tract cancer [45].…”
Section: Discussionsupporting
confidence: 52%
“…By performing IHC staining assay with primary and metastatic ovarian cancer tissues and survival analysis, we further proved that PD‐L1 could be regarded as a prognostic risk factor and induce ovarian cancer progression and metastasis. Previous studies have reported similar results in other types of cancer, such as head and neck cancer [41], colorectal cancer [42], endometrial cancer [43], and clear cell renal cell carcinoma [44]. PD‐L1 was also found to play a vital role as a poor prognosis predictor in patients with biliary tract cancer [45].…”
Section: Discussionsupporting
confidence: 52%
“…However, the recurrence rate of CRC within 2 years after undergoing radical resection has been reported to be high (nearly 50%), and half of the relapses were fatal [2]. Immunotherapy, especially inhibitors targeting immune checkpoints, including cytotoxic T-lymphocyte antigen-4 (CTLA4), programmed cell death protein 1 (PD-1), and programmed cell death 1 ligand 1 (PD-L1), has provided promising new approaches to improve the overall survival (OS) of patients with CRC [3][4][5][6]. In particular, recent studies have demonstrated that pembrolizumab (an anti-PD-1 monoclonal antibody) had improved efficacy and long-term clinical benefit for the subgroup of patients with microsatellite instability-high (MSI-H)/DNA mismatch repair-deficient (dMMR) CRC [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, multivariate analysis showed that PD-L1 expression was a predictive marker for OS in the entire cohort. Analogously, a recent large metaanalysis by Wang et al [39] in a large cohort of 8823 CRC patients from 32 studies also showed that PD-L1 expression was an independent predictor for poor OS. Another metaanalysis comprising 13 studies with 3905 CRC patients also showed a significant association between expression of PD-L1 and poor OS [40].…”
Section: Discussionmentioning
confidence: 72%